Analysis Before And After The Covid-19 Pandemic On Profitability In Bank - Nabella Novia Putri; Metageissa Dwiputri; Neng Wulan; Irwan Hermawan (West Science Business and Management, 2023)
Banking profitability is the most important thing in the financial system for the economy in Indonesia (developing countries) in the future, because profitability is a ratio that shows the ability to earn profits or profits. The level of income earned in banking is influenced by external factors and internal factors. The purpose of this study is to determine whether or not there is a decrease in the income obtained by banks during the Covid-19 pandemic and the comparison of profits obtained before and after the Covid-19 pandemic. Even though the Covid-19 pandemic is not yet one year old, it has brought many bad effects, Meanwhile, the results of research on the analysis of profit comparisons using the profitability ratio method produce data, namely that there is a significant decrease in earnings reaching 40% from the previous year period. This decline is considered to be the greatest from the previous year period.